Changes in calcium dynamics following the reversal of the sodium-calcium exchanger have a key role in AMPA receptor-mediated neurodegeneration via calpain activation in hippocampal neurons - Araújo, I. M. (2007)
Proteolytic cleavage of the Na(+)/Ca(2+) exchanger (NCX) by calpains impairs calcium homeostasis, leading to a delayed calcium overload and excitotoxic cell death. However, it is not known whether reversal of the exchanger contributes to activate calpains and trigger neuronal death. We investigated the role of the reversal of the NCX in Ca(2+) dynamics, calpain activation and cell viability, in alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptor-stimulated hippocampal neurons. Selective overactivation of AMPA receptors caused the reversal of the NCX, which accounted for approximately 30% of the rise in intracellular free calcium concentration ([Ca(2+)](i)). The NCX reverse-mode inhibitor, 2-[2-[4-(4-nitrobenzyloxy)phenyl]ethyl]isothiourea (KB-R7943), partially inhibited the initial increase in [Ca(2+)](i), and prevented a delayed increase in [Ca(2+)](i). In parallel, overactivation of AMPA receptors strongly activated calpains and led to the proteolysis of NCX3. KB-R7943 prevented calpain activation, cleavage of NCX3 and was neuroprotective. Silencing of NCX3 reduced Ca(2+) uptake, calpain activation and was neuroprotective. Our data show for the first time that NCX reversal is an early event following AMPA receptor stimulation and is linked to the activation of calpains. Since calpain activation subsequently inactivates NCX, causing a secondary Ca(2+) entry, NCX may be viewed as a new suicide substrate operating in a Ca(2+)-dependent loop that triggers cell death and as a target for neuroprotection